MCX: a Synchrotron Radiation Beamline for X‐ray Diffraction Line Profile Analysis. Issue 15 (12th June 2014) - Rebuffi, Luca; Plaisier, Jasper R.; Abdellatief, Mahmoud; Lausi, Andrea; Scardi, Paolo
Abstract The potential of modern methods for X‐ray diffraction Line Profile Analysis can be fully exploited with data collected at synchrotron radiation beamlines, provided that optics and experimental set‐up are suitably designed and characterized. The Material Characterization by X‐ray Diffraction beamline, MCX, at Elettra‐Sincrotrone Trieste, may operate with a set‐up optimally arranged to study nanostructured materials, investigating details of crystalline domain size and shape, lattice defects, and local atomic displacement of static and dynamic nature. Main features of MCX are briefly discussed and best operating conditions illustrated by representative case studies.